Anxiety at 13 and its effect on pain, pain-related anxiety, and pain-related disability at 17: An ALSPAC cohort longitudinal analysis. Issue 1 (2nd January 2016) - Fisher, Emma; Caes, Line; Clinch, Jacqui; Tobias, Jon H.; Eccleston, Christopher
Abstract : The aim of the present study was to investigate the influence of anxiety at 13 years of age on the presence of chronic pain, pain-related anxiety, and pain-related disability at 17 years of age in a large longitudinal cohort. We hypothesized that mother-reported anxiety at 13 would be associated with the presence of chronic pain at 17 and an increase in pain-related anxiety using all available data from the longitudinal cohort. Further, we hypothesized that anxiety at 13 would predict pain-related disability in adolescents who reported chronic pain at 17 years of age. Participants were recruited from the Avon Longitudinal Study of Parents and Children based in the UK who attended a university research clinic at 17. Child anxiety (reported by the mother) was extracted at child age 13, and self-report of the presence of chronic pain, pain-related anxiety, and pain-related disability at 17. Analyses revealed that child anxiety at 13 was not significantly associated with the presence of chronic pain at 17 ( n  = 842). However, anxiety at 13 was significantly associated with pain-related anxiety at 17 ( n  = 1831). For the subsample of adolescents who reported chronic pain, anxiety at 13 was associated with pain-related disability at 17 ( n  = 393). Further analyses revealed that pain-related anxiety at 17 mediated the association between anxiety at 13 and pain-related disability at 17, suggesting that pain-related anxiety should be a target for treatment in adolescents with chronic pain, to reduce the impact of pain in later adolescence. General anxiety at 13 was unrelated to the presence of chronic pain at 17, but should be considered a risk factor for later pain-related anxiety and disability in a subset of adolescents who develop chronic pain.